Allogeneic Matched Related Donor Bone Marrow Transplantation for Pediatric Patients With Severe Aplastic Anemia Using "Low-dose" Cyclophosphamide, ATG Plus Fludarabine. Issue 4 (May 2018) - Takpradit, Chayamon; Prockop, Susan E.; Kernan, Nancy A.; Scaradavou, Andromachi; Curran, Kevin; Ruggiero, Julianne; Zakak, Nicole; O'Reilly, Richard J.; Boulad, Farid
Abstract : Background: The combination of cyclophosphamide (CY) and antithymocyte globulin (ATG) has been used as a standard conditioning regimen for matched related donor transplantation in patients with severe aplastic anemia. Procedure: To decrease the regimen-related toxicity while maintaining appropriate engraftment and survival rates, fludarabine (FLU) was added to the regimen. Four pediatric patients received matched related donor bone marrow transplantation with CY (50 mg/kg×2) (instead of the 50 mg/kg×4 standard dosing), equine ATG (30 mg/kg×3), with the addition of FLU (30 mg/m 2 ×4). Graft versus host disease (GvHD) prophylaxis included a calcineurin inhibitor and methotrexate. Results: No grade 4 acute toxicities occurred during the first 30 days after transplant. All patients engrafted with normalization of peripheral blood counts and transfusion independence. One patient developed grade 1 to 2 acute GvHD, followed by chronic GvHD that resolved. With a median follow-up of 41.7 months, all 4 patients are alive and transfusion free, with complete donor chimerism. This combination of a low-dose CY/ATG+FLU regimen was overall very well tolerated and contributed toward a successful outcome including engraftment, chimerism, and survival. Conclusion: This small pilot study shows that this cytoreductive regimen could be considered as the standard of care for transplantation of pediatric patients with aplastic anemia from HLA-matched siblings.